Unmanned Aerial Vehicles Platforms, Applications, Security and Services - Calafate, Carlos Tavares; Tropea, Mauro (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The use of unmanned aerial vehicles (UAVs) plays an important role in supporting human activities. Man is concentrating more and more on intellectual work, and trying to automate practical activities as much as possible in order to increase their efficiency. In this regard, the use of drones is increasingly becoming a key aspect of this automation process, offering many advantages, including agility, efficiency and reduced risk, especially in dangerous missions. Hence, this Special Issue focuses on applications, platforms and services where UAVs can be used as facilitators for the task at hand, also keeping in mind that security should be addressed from its different perspectives, ranking from communications security to operational security, and furthermore considering privacy issues.